Evaluasi Pemanfaatan Aplikasi Warmadewa e-Library - Ayu Dirgantari, Ni Kadek Sri Devi; Suhartika, I Putu; Ginting, Richard Togranta (Jurnal Ilmiah Ilmu Perpustakaan dan Informasi, 2021)
The purpose of this study was to evaluate the use of thedigital library application Warmadewa e-Library at the UPT Perpsutakaan Warmadewa University. This type of research uses a quantitative descriptive method. The total population of this study was taken from the list of members registered in the Warmadewa e-Library Application, which amounted to 242 people and the number of samples was 70 people which was calculated using the Slovin formula. Determination of the sample from this study using  probability sampling technique with aapproach purposive sampling. This study uses webqual 4.0 in distributing questionnaires. There are three categories that are used as references, namely usability, quality of information, service interaction in making a questionnaire to evaluate the use of theapplication Warmadewa e-Library. With these three references, it is expected to be able to increase the use of theapplication Warmadewa e-Libraryin the future. Keywords: Warmadewa e-Library, Digital Library Application, Webqual 4.0